The Relationship Between Governance and Economic Growth During Times of Crisis - AlBassam, Bassam A. (European Journal of Sustainable Development, 2013)
The current economic crisis has affected all aspects of life, resulting in political instability,personal financial troubles, and a growing number of business bankruptcies. Although these areserious issues, simply developing a government policy that injects an economy with money is notan appropriate means to achieve economic recovery and long-term economic development unlesscombined with an effective and efficient governing system. The present article examines whetherthe strong relationship between governance and growth exists during economic crises or onlyduring non-crisis periods. The results of the current paper demonstrate that the global economiccrisis has had an unnoticeable influence on the relationship between governance and economicgrowth. However, this study found that different levels of development of nations affect therelationship between governance and growth in various ways during times of crisis. Thus, theresults of the current paper highlight the instability in the relationship between governance andeconomic growth during the economic crisis; this unsteadiness is a sign of the need for long-termstrategies to promote global and national good governance practices that are not adverselyaffected by crises.